Fungsi Aizuchi Verbal dalam Dialog Anime Yuru Camp Episode 1-6 Karya Afro - Aryandi, Arif Dzaki; Andarwati, Titien Wahyu (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2023)
Aizuchi (backchannel) is one of the unique habits that Japanese people have when talking to others. Aizuchi is a short phrase said by listeners when having a conversation. There are seven functions of aizuchi according Mayumi Kubota. Yuru Camp is one of the anime that applies a lot of aizuchi habits. That is what makes researchers interested in researching the function of aizuchi contained in Yuru Camp by Afro. The purpose of this study is to describe the function of aizuchi contained in the Yuru Camp. This research is a descriptive qualitative research and the analysis uses aizuchi theory proposed by Mayumi Kubota.. In this research, it is found that the functions of aizuchi used in Yuru Camp anime dialog are hearing sign (kiite iru to iu shingou), understanding sign (rikai shite iru to iu shingou), agreement sign (doui no shingou), denial sign (hitei no shingou), (kanjou no shingou), pause mark (ma o motaseru shingou), and adding, correcting, and requesting information (jouhou o tsuika, teisei, youkyuu no shingou). The use of aizuchi in the Yuru Camp anime supports smooth conversations between characters because the listener shows his attention to the speaker in a polite way. Keywords: aizuchi; anime; verbal.